A kind of full water foamed polyurethane for heat insulation pipe and preparation method thereof

By using a combination of various polyether polyols and catalysts in polyurethane materials, the degree of crosslinking and pore size uniformity of the polymer are improved, and the core cracking and environmental problems of the whole water foamed polyurethane material are solved, achieving high mechanics Preparation of polyurethane foam materials that are capable of being environmentally friendly.

CN115991860BActive Publication Date: 2025-01-03TIANJIN AIDEJIA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211422685.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-14
Publication Date
2025-01-03
Estimated Expiration
2042-11-14

AI Technical Summary

Technical Problem

The existing polyurethane insulation materials are prone to core cracking during the whole water foaming process, and the lack of physical foaming agents leads to high viscosity and fast reaction speed of the reaction system, resulting in environmental problems and insufficient performance.

Method used

A variety of polyether polyols with different functionalities and hydroxyl values ​​react with polymethyl polyphenyl polyisocyanate to increase the structure of carbamate chain segments and hard segments, improve the cross-linking degree and pore size uniformity of the polymer, through Modified materials such as catalysts and fibers enhance the mechanical properties of foam.

Benefits of technology

The all-water foamed polyurethane foam produced has high mechanical properties and is not prone to core cracking. It is suitable for large pipe insulation pipes, and is environmentally friendly and has no greenhouse effect. It is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003942635330000091
    Figure BDA0003942635330000091
  • Figure BDA0003942635330000101
    Figure BDA0003942635330000101
Patent Text Reader

Abstract

The present application relates to the field of polymer thermal insulation materials, and specifically discloses a fully water-foamed polyurethane for thermal insulation pipes and a preparation method thereof. The raw materials used for polyurethane include black material and white material, wherein the black material is polymethyl polyphenyl polyisocyanate, and the white material includes polyether polyol A-E, a catalyst, a foam stabilizer and water; its preparation method is: S1. All components in the white material are mixed evenly to obtain a mixture; S2. Under the conditions of a temperature of 15-35°C and a rotation speed of 2500-2600r / min, the mixture is mixed and stirred evenly with the black material to obtain polyurethane foam. The polyurethane foam of the present application uses water as a foaming agent, is green and environmentally friendly, has a low odor during the foaming process, and has high mechanical properties, and is not easy to burn the core and crack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer thermal insulation materials, and more specifically, to a full water foamed polyurethane for thermal insulation pipes and a preparation method thereof. Background Art

[0002] Insulated pipes are widely used in the transportation of central heating, cooling and hot oil, as well as the insulation and cold preservation projects of greenhouses, cold storages, coal mines, petrochemicals and other industries. They are suitable for conveying various media within the range of -50 to 150°C. The insulation pipe consists of three parts from the inside to the outside: the working steel pipe, the insulation layer and the protective pipe. The working steel pipe is used to convey the medium; the protective pipe is mostly made of high-density polyethylene material, which mainly plays a protective role during transportation, installation and use; the insulation layer is the key part that makes the insulation pipe have insulation performance, which can maintain the temperature of the medium conveyed by the pipeline, and also has the function of improving the overall ring stiffness of the insulation pipe.

[0003] Polyurethane foam material has become the most commonly used insulation material in the world due to its good physical and mechanical properties, insulation performance and high specific strength. It is widely used in the production of insulation layers in insulated pipes. The existing production processes of polyurethane insulation layers are mainly divided into spraying and injection molding. Since the spraying method has the advantages of uniform foaming, low viscosity and high foaming rate, it is widely used in the production of insulation layers of large insulated pipes (inner pipe diameter>0.8m).

[0004] Traditional polyurethane foam materials are generally prepared by reacting polyether polyols and isocyanates under the action of chlorofluorocarbon physical foaming agents. However, such physical foaming agents have high ozone depletion values, which will damage the ozone layer and cause environmental problems such as the greenhouse effect. Therefore, the green foaming route is currently adopted, that is, water is used as a foaming agent to prepare polyurethane foam materials. However, since the fully water-foamed polyurethane foam lacks the dilution of a physical foaming agent, the viscosity of the reaction system is relatively high, and the reaction speed of the foaming reaction process is relatively fast and the heat release is relatively large, which is prone to problems such as core burning and cracking. Therefore, the inventor believes that it is very necessary to study a fully water-foamed polyurethane insulation material with high mechanical properties and not easy to burn and crack the core. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a full water foamed polyurethane for thermal insulation pipes and a preparation method thereof.

[0006] In the first aspect, the present application provides a fully water-foamed polyurethane for heat-insulating pipes, which adopts the following technical scheme: a fully water-foamed polyurethane for heat-insulating pipes, characterized in that the raw materials used for the polyurethane include black material and white material in a weight ratio of (100-150):100; the black material is polymethyl polyphenyl polyisocyanate;

[0007] The white material comprises the following components in parts by weight:

[0008] Polyether polyol A 30-50 parts;

[0009] Polyether polyol B 10-20 parts;

[0010] Polyether polyol C10-50 parts;

[0011] Polyether polyol D 10-20 parts;

[0012] Polyether polyol E 0-20 parts;

[0013] 2-8 parts of catalyst;

[0014] Foam stabilizer 1-3 parts;

[0015] 1-3 parts water;

[0016] The polyether polyol A has a functionality of 4.5-6, a hydroxyl value of 360-450 mgKOH / g, and a viscosity of 5000-12000 map·s;

[0017] The polyether polyol B has a functionality of 3-5, a hydroxyl value of 500-1200 mgKOH / g, and a viscosity of 600-1600 map·s;

[0018] The polyether polyol has a C functionality of 3.5-4.5, a hydroxyl value of 320-380 mgKOH / g, and a viscosity of 700-1500 map·s;

[0019] The polyether polyol D has a functionality of 3-4, a hydroxyl value of 300-500 mgKOH / g, and a viscosity of 2000-4000 map·s;

[0020] The polyether polyol E has a functionality of 2-3, a hydroxyl value of 300-400 mgKOH / g, and a viscosity of 2000-30000 map·s.

[0021] By adopting the above technical scheme, in the present application, the polymethyl polyphenyl polyisocyanate adopts Huntsman's isocyanate 5005; polyether polyol A is polyether polyol A formed by polymerization of propylene oxide with sucrose and diethylene glycol as initiators; polyether polyol B is polyether polyol B formed by polymerization of propylene oxide with glycerol as initiator; polyether polyol C is polyether polyol C formed by polymerization of propylene oxide with ethylene glycol as initiator; polyether polyol D is polyether polyol D formed by polymerization of ethylene oxide with glycerol as initiator; polyether polyol E is polyether polyol E formed by polymerization of phthalic anhydride-diethylene glycol.

[0022] The present application adopts a mixture of polyether polyols with different functionalities and hydroxyl values ​​to react with polymethyl polyphenyl polyisocyanate, so that a larger number of carbamate segments are formed in the polymer matrix, and the number of hard segment structures in the polymer matrix is ​​increased; at the same time, the number of stereopolymers in the polyurethane foam polymer matrix obtained by the reaction is increased, and the number of linear polymers is reduced, so that the overall cross-linking degree of the polymer resin in the polyurethane foam is higher, thereby significantly enhancing the mechanical properties of the polyurethane foam, and the obtained polyurethane thermal insulation material is not easy to burn and crack.

[0023] In addition, the present application also utilizes the collocation of different functionalities and hydroxyl values ​​between multiple polyether polyols, accelerates the growth rate and gel reaction speed of macromolecular chains, shortens the curing time of polyurethane foam, and when the bubbles in the reaction process have not yet reached the maximum, the matrix resin has been cross-linked into a network structure, and solid foam has been formed, so that the average pore size of polyurethane foam is reduced. According to the foam forming theory, the foam pore size decreases, the pillar of the bubble film pore size increases, the ability to resist external deformation is enhanced, and the mechanical property of polyurethane foam is enhanced. Meanwhile, the premature loss of viscoelasticity of the cell wall of polyurethane foam in the reaction process reduces the occurrence of drainage and bubble phenomenon, reduces the probability of large bubble generation in polyurethane foam, thereby improving the uniformity of polyurethane foam pore size, and further enhancing the mechanical property of polyurethane foam.

[0024] In addition, the thicker the insulation layer, the greater the heat released by the full water foaming, and the easier it is for the insulation layer to burn and crack. The polyurethane foam of the present application is suitable for the production of large-diameter insulated pipes of 1420-1620 cm. The insulation layer formed by it can be 150 mm thick without burning and cracking, has a smooth surface, and has low odor.

[0025] In summary, the present application increases the number of hard segment structures in the polymer matrix, enhances the overall cross-linking degree of the polymer resin in the polyurethane foam, reduces the average pore size of the polyurethane foam, improves the uniformity of the pore size of the polyurethane foam, and improves the mechanical properties of the polyurethane foam from two aspects: the chemical structure of the polyurethane matrix resin and the pore structure of the polyurethane foam, so that the obtained polyurethane thermal insulation material is not easy to burn and crack at a larger thickness.

[0026] Preferably, the weight ratio of the black material to the white material is (135-140):100.

[0027] By adopting the above technical solution, the present application further controls the weight ratio between the black material and the white material, further enhances the mechanical properties of the polyurethane foam, and makes the prepared polyurethane foam insulation material less prone to core burning and cracking.

[0028] Preferably, the catalyst comprises dibutyltin dilaurate, pentamethyldiethylenetriamine, N,N-dimethylcyclohexylamine, tris(dimethylaminopropyl)hexahydrotriazine, Dabco 33-LV and potassium acetate catalyst in a weight ratio of (0.01-0.02):(0.1-2):(0.1-3):(0.1-4):(0.1-3):(0.1-2).

[0029] By adopting the above-mentioned technical scheme, the present application adopts a mixed and matched use of multiple catalysts, which can increase the gelation speed of the polyurethane foam, accelerate the post-maturation of the polyurethane foam, balance the entire foaming process, make the foaming reaction proceed smoothly, improve the mechanical properties of the polyurethane foam, and at the same time reduce the possibility of affecting the surface flatness of the polyurethane foam due to too fast a rising speed.

[0030] Preferably, the white material further comprises 1.08-4.38 parts by weight of hollow glass microspheres and 1.35-5.47 parts by weight of jute fibers modified with a silane coupling agent.

[0031] By adopting the above technical solution, the present application adds hollow glass microspheres and jute fibers to the white material, which can significantly improve the pore structure of the polyurethane foam, enhance the stability of the bubbles, and improve the uniformity of the pore size of the polyurethane foam, thereby improving the mechanical properties of the polyurethane foam.

[0032] The present application uses a silane coupling agent to modify jute fiber, which can enhance the interface meshing and bonding between jute fiber and polyurethane matrix resin, and further improve the degree of mechanical properties of jute fiber reinforced polyurethane foam. The silane coupling agent of the present application is silane coupling agent KH550, and the specific modification method is: immersing jute fiber in a mixed solution of silane coupling agent KH550, anhydrous ethanol and distilled water in a volume ratio of 1:9:1, ultrasonically dispersing for 30-40 minutes, and then stirring for 8 hours at a temperature of 70-75°C, filtering, washing, and drying to obtain modified jute fiber.

[0033] Preferably, the hollow glass microspheres are modified by the following method:

[0034] First, the hollow glass microspheres are immersed in acetone, and then the hollow glass microspheres are taken out and dried at a temperature of 110-120°C. After that, the hollow glass microspheres are soaked in a silane coupling agent with a mass fraction of 0.5-2% for 15-20 minutes, and then filtered and dried at a temperature of 110-120°C for 1-2 hours to obtain modified hollow glass microspheres.

[0035] By adopting the above technical solution, the present application uses a silane coupling agent to modify the hollow glass microspheres, thereby improving the bonding force between the hollow glass microspheres and the polyurethane foam matrix resin, enhancing the interface strength, and further improving the pore structure of the polyurethane foam, thereby further improving the mechanical properties of the polyurethane foam. The silane coupling agent of the present application uses silane coupling agent KH550.

[0036] Preferably, the jute fiber has a chopped length of 1.8-2.0 mm.

[0037] By adopting the above technical solution, the present application further controls the short cut length of the jute fiber within a specific range, making the jute fiber easier to mix evenly in the polyurethane foam, reducing the possibility that the jute fiber is difficult to combine with the polyurethane matrix resin due to being too long, thereby further improving the mechanical properties of the polyurethane foam.

[0038] Preferably, the white material further comprises 1.5-4.5 parts by weight of carbon nanotubes.

[0039] By adopting the above technical solution, the present application also adds carbon nanotubes to the white material, so that the pore size and distribution of the polyurethane foam are uniform, the pore wall strength is increased, and the foam pore structure is more complete, thereby improving the mechanical properties of the polyurethane foam.

[0040] Preferably, the carbon nanotubes are amino-treated carbon nanotubes.

[0041] By adopting the above technical solution, the present application further adopts amino-modified carbon nanotubes, which can significantly improve the dispersibility of carbon nanotubes in the polyurethane foam matrix resin and enhance the interaction between the carbon nanotubes and the matrix resin, thereby further improving the pore structure of the polyurethane foam and enhancing the mechanical properties of the polyurethane foam.

[0042] Preferably, the foam stabilizer is a silicon-based surfactant.

[0043] By adopting the above technical solution, the silicon-based surfactant of the present application has good emulsification and dispersing effects, and can enable the polyurethane foam to form a good pore structure.

[0044] In a second aspect, the present application provides a method for preparing a fully water-foamed polyurethane for an insulation pipe, comprising the following steps: S1. uniformly mixing all components in a white material to obtain a mixture;

[0045] S2. Under the conditions of a temperature of 15-35°C and a rotation speed of 2500-2600r / min, the mixed material and the black material are mixed and stirred evenly to obtain a fully water-foamed polyurethane.

[0046] By adopting the above technical solution, the present application can spray after the white material and the black material are evenly mixed, and the formed polyurethane foam insulation layer has high mechanical strength, can resist the heat released during the foaming process, and is not easy to burn the core and crack. In addition, the preparation method is simple in steps, easy to operate, and suitable for large-scale industrial production.

[0047] In summary, the present application includes at least one of the following beneficial technical effects:

[0048] 1. The base resin of the polyurethane foam of the present application has a high degree of cross-linking, the foam pore size and distribution are uniform, the pore structure is good, and the mechanical properties are strong. It is suitable for the production of large-diameter insulation pipes of 1420-1620cm. The insulation layer formed by it has a thickness of 150mm and does not have the phenomenon of core burning and cracking;

[0049] 2. The polyurethane foam of the present application uses water as a foaming agent, which is green and environmentally friendly, is not likely to cause environmental problems such as the greenhouse effect, and has a low foaming odor;

[0050] 3. The polyurethane foam preparation method of the present application is simple, easy to operate, and suitable for large-scale industrial production. DETAILED DESCRIPTION

[0051] <Material source>

[0052] The polyether polyols AE of this application are all commercially available products;

[0053] The polymethyl polyphenyl polyisocyanate of the present application is produced by Huntsman, model 5005;

[0054] The dibutyltin dilaurate of the present application is produced by Air Products and Chemicals of the United States, model Dabco T 120;

[0055] The pentamethyldiethylenetriamine of the present application is produced by Air Products and Chemicals of the United States, model number Polycat 5;

[0056] The N,N-dimethylcyclohexylamine of the present application is produced by Air Products and Chemicals of the United States, model number Polycat 8;

[0057] The tris(dimethylaminopropyl)hexahydrotriazine of the present application is produced by Air Products and Chemicals of the United States, model number Polycat 41;

[0058] Dabco 33-LV of the present application is produced by Air Products and Chemicals of the United States and is formulated with 33% triethylenediamine and 67% dipropylene glycol;

[0059] The potassium acetate catalyst of the present application is produced by Air Products and Chemicals of the United States, model number Polycat 46;

[0060] The silicone surfactant of the present application is produced by Momentive, model L-6900;

[0061] The amino-modified carbon nanotubes of the present application were purchased from Beijing Dekedaojin Technology Co., Ltd., with an amino content of 0.45 wt % and an outer diameter of 8-15 nm.

[0062] <Preparation example>

[0063] Preparation Example 1

[0064] Hollow glass microspheres are modified by the following methods:

[0065] First, 10 kg of hollow glass microspheres were immersed in acetone, and then the hollow glass microspheres were taken out and dried at a temperature of 110°C. After that, the hollow glass microspheres were soaked in a silane coupling agent KH550 with a mass fraction of 0.5% for 15 minutes, and then filtered and dried at a temperature of 110°C for 1 hour to obtain modified hollow glass microspheres.

[0066] Preparation Example 2

[0067] Hollow glass microspheres are modified by the following methods:

[0068] First, 10 kg of hollow glass microspheres were immersed in acetone, and then the hollow glass microspheres were taken out and dried at a temperature of 110°C. After that, the hollow glass microspheres were soaked in a silane coupling agent KH550 with a mass fraction of 0.5% for 15 minutes, and then filtered and dried at a temperature of 110°C for 1 hour to obtain modified hollow glass microspheres.

[0069] Preparation Example 3

[0070] Jute fiber is modified by the following methods:

[0071] 10 kg of jute fiber was immersed in a mixture of 1 L of silane coupling agent KH550, 9 L of anhydrous ethanol and 1 L of distilled water, and ultrasonically dispersed for 30-40 minutes, and then continuously stirred for 8 hours at a temperature of 70-75° C., and then filtered, washed and dried to obtain modified jute fiber.

[0072] <Example>

[0073] Example 1

[0074] A method for preparing a fully water-foamed polyurethane for a thermal insulation pipe comprises the following steps:

[0075] S1. 50 kg of polyether polyol A, 10 kg of polyether polyol B, 22.49 kg of polyether polyol C, 10 kg of polyether polyol D, 4.51 kg of catalyst (0.01 kg of dibutyltin dilaurate, 1 kg of pentamethyldiethylenetriamine, 0.5 kg of N,N-dimethylcyclohexylamine, 0.5 kg of tris(dimethylaminopropyl)hexahydrotriazine, 2 kg of Dabco 33-LV, 0.5 kg of potassium acetate catalyst), 2 kg of silicon surfactant L-6900 and 2 kg of water were mixed to obtain a mixture;

[0076] S2. At a temperature of 20°C and a rotation speed of 2500 r / min, 101 kg of the mixture was mixed and stirred evenly with 67.3 kg of polymethyl polyphenyl polyisocyanate to obtain a fully water-foamed polyurethane.

[0077] Example 2

[0078] A method for preparing a fully water-foamed polyurethane for a thermal insulation pipe comprises the following steps:

[0079] S1. 30kg of polyether polyol A, 20kg of polyether polyol B, 50kg of polyether polyol C, 20kg of polyether polyol D, 20kg of polyether polyol E, 2kg of catalyst (0.04kg of dibutyltin dilaurate, 0.392kg of pentamethyldiethylenetriamine, 0.392kg of N,N-dimethylcyclohexylamine, 0.392kg of tris(dimethylaminopropyl)hexahydrotriazine, 0.392kg of Dabco 33-LV, 0.392kg of potassium acetate catalyst), 1kg of silicon surfactant L-6900 and 1kg of water were mixed to obtain a mixture;

[0080] S2. At a temperature of 15°C and a rotation speed of 2600 r / min, 144 kg of the mixture and 144 kg of polymethyl polyphenyl polyisocyanate were mixed and stirred uniformly to obtain a fully water-foamed polyurethane.

[0081] Example 3

[0082] A method for preparing a fully water-foamed polyurethane for a thermal insulation pipe comprises the following steps:

[0083] S1. 40kg of polyether polyol A, 15kg of polyether polyol B, 10kg of polyether polyol C, 15kg of polyether polyol D, 10kg of polyether polyol E, 8kg of catalyst (0.012kg of dibutyltin dilaurate, 1.141kg of pentamethyldiethylenetriamine, 1.712kg of N,N-dimethylcyclohexylamine, 2.282kg of tris(dimethylaminopropyl)hexahydrotriazine, 1.712kg of Dabco 33-LV, 1.141kg of potassium acetate catalyst), 3kg of silicon surfactant L-6900 and 3kg of water were mixed to obtain a mixture;

[0084] S2. At a temperature of 35°C and a rotation speed of 2550 r / min, 104 kg of the mixture and 104 kg of polymethyl polyphenyl polyisocyanate were mixed and stirred uniformly to obtain a fully water-foamed polyurethane.

[0085] Example 4

[0086] A method for preparing fully water-foamed polyurethane for heat-insulating pipes, which is different from Example 1 in that: in step S2, the amount of polymethyl polyphenyl polyisocyanate used is 74.8 kg.

[0087] Example 5

[0088] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which is different from Example 1 in that: in step S2, the amount of polymethyl polyphenyl polyisocyanate used is 72.1 kg.

[0089] Example 6

[0090] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which differs from Example 1 in that: 1.08 kg of hollow glass microspheres and 5.47 kg of jute fibers (with a short chopped length of 0.5-1.5 mm) prepared in Preparation Example 3 are also added to the mixture in Step S1.

[0091] Example 7

[0092] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which differs from Example 1 in that: 4.38 kg of hollow glass microspheres and 1.35 kg of jute fibers (with a short chopped length of 2.2-2.5 mm) prepared in Preparation Example 3 are also added to the mixture in Step S1.

[0093] Example 8

[0094] A method for preparing fully water-foamed polyurethane for heat-insulating pipes, which is different from Example 7 in that the hollow glass microspheres use the modified hollow glass microspheres prepared in Preparation Example 1.

[0095] Example 9

[0096] A method for preparing all-water foamed polyurethane for thermal insulation pipes, which is different from Example 7 in that the hollow glass microspheres use the modified hollow glass microspheres prepared in Preparation Example 2.

[0097] Example 10

[0098] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which is different from Example 7 in that the short cut length of the jute fiber is 1.8-2.0 mm.

[0099] Embodiment 11

[0100] A method for preparing all-water foamed polyurethane for heat-insulating pipes is different from that of Example 1 in that 1.5 kg of carbon nanotubes are also added to the mixture in step S1.

[0101] Example 12

[0102] A method for preparing all-water foamed polyurethane for heat-insulating pipes is different from that of Example 1 in that 4.5 kg of carbon nanotubes are also added to the mixture in step S1.

[0103] Embodiment 13

[0104] A method for preparing all-water foamed polyurethane for thermal insulation pipes, which is different from Example 12 in that the carbon nanotubes are amino-treated carbon nanotubes.

[0105] Embodiment 14

[0106] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which is different from Example 1 in that: the catalyst in step S1 only uses a mixture of 2.255 kg of pentamethyldiethylenetriamine, 1.1275 kg of N,N-dimethylcyclohexylamine and 1.1275 kg of potassium acetate catalyst.

[0107] Embodiment 15

[0108] A method for preparing a fully water-foamed polyurethane for an insulation pipe is different from that of Example 1 in that: the catalyst in step S1 is a mixture of only 3.608 kg of Dabco 33-LV and 0.902 kg of tris(dimethylaminopropyl)hexahydrotriazine.

[0109] Example 16

[0110] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which is different from Example 1 in that: the Dabco 33-LV in the catalyst in step S1 is replaced by a catalyst BDMA purchased from Xindian Chemical Materials (Shanghai) Co., Ltd.

[0111] Embodiment 17

[0112] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which is different from Example 1 in that: the N,N-dimethylcyclohexylamine in the catalyst in step S1 is replaced by a catalyst Polycat 8 purchased from Xindian Chemical Materials (Shanghai) Co., Ltd.

[0113] Embodiment 18

[0114] A method for preparing a fully water-foamed polyurethane for an insulation pipe, which is different from Example 1 in that: 0.08 kg of hollow glass microspheres and 8 kg of jute fibers prepared in Preparation Example 3 are also added to the mixture in step S1.

[0115] Embodiment 19

[0116] A method for preparing fully water-foamed polyurethane for heat-insulating pipes, which is different from Example 1 in that: 6 kg of hollow glass microspheres and 1 kg of jute fiber prepared in Preparation Example 3 are also added to the mixture in step S1.

[0117] Embodiment 20

[0118] A method for preparing all-water foamed polyurethane for heat-insulating pipes is different from that of Example 1 in that 1 kg of carbon nanotubes is also added to the mixture in step S1.

[0119] Embodiment 21

[0120] A method for preparing all-water foamed polyurethane for heat-insulating pipes is different from that of Example 1 in that 6 kg of carbon nanotubes are also added to the mixture in step S1.

[0121] <Comparative example>

[0122] Comparative Example 1

[0123] The difference from Example 1 is that polyether polyol A, polyether polyol B and polyether polyol C are not added to the mixed material in step S1.

[0124] Comparative Example 2

[0125] The difference from Example 1 is that polyether polyol A and polyether polyol C are not added to the mixed material in step S1.

[0126] Comparative Example 3

[0127] The difference from Example 1 is that polyether polyol B and polyether polyol D are not added to the mixed material in step S1.

[0128] Comparative Example 4

[0129] The difference from Example 1 is that polyether polyol A and polyether polyol D are not added to the mixture in step S1.

[0130] Comparative Example 5

[0131] The difference from Example 1 is that polyether polyol A is not added to the mixed material in step S1.

[0132] Comparative Example 6

[0133] The difference from Example 1 is that in the mixed material of step S1, polyether polyol A is 10 kg, polyether polyol B is 30 kg, polyether polyol C is 5 kg, and polyether polyol D is 25 kg.

[0134] Comparative Example 7

[0135] The difference from Example 1 is that in the mixed material of step S1, polyether polyol A is 60 kg, polyether polyol B is 7 kg, polyether polyol C is 65 kg, and polyether polyol D is 2 kg.

[0136] Comparative Example 8

[0137] The difference from Example 1 is that in step S2, the amount of polymethyl polyphenyl polyisocyanate used is 202 kg.

[0138] Comparative Example 9

[0139] The difference from Example 1 is that in step S2, the amount of polymethyl polyphenyl polyisocyanate used is 50.5 kg.

[0140] <Performance test>

[0141] 1. The compressive strength (MPa) of the polyurethane foams prepared in the examples and comparative examples was measured with reference to GB / T 8813-2008 "Determination of compression properties of rigid foam plastics". The results are shown in Table 1.

[0142] 2. The thermal conductivity (W / (m·k)) of the polyurethane foams prepared in the examples and comparative examples at 50°C was measured with reference to GB / T 20219-2015 "Sprayed rigid polyurethane foam for thermal insulation". The results are shown in Table 1.

[0143] 3. Observe whether the surfaces of the polyurethane foams prepared in the examples and comparative examples are cracked. The results are shown in Table 1.

[0144] Table 1 Performance test results

[0145]

[0146]

[0147] It can be seen from Table 1 that the compressive strength of the polyurethane foams prepared in Examples 1-3 of the present application is between 0.489-0.538 MPa, and the thermal conductivity is between 0.0293-0.0301 W / (m·k), which has high mechanical properties. In addition, the surface of the polyurethane foam is smooth without core burning and cracking.

[0148] The compressive strength of Examples 4-5 is higher than that of Example 1, and the thermal conductivity is lower than that of Example 1, indicating that the present application further controls the weight ratio between the black material and the white material, and can further improve the mechanical properties of the polyurethane foam.

[0149] The compressive strength of Examples 6-7 is higher than that of Example 1, and the thermal conductivity is lower than that of Example 1, indicating that the addition of hollow glass microspheres and modified jute fibers to the white material in the present application can significantly improve the mechanical properties of the polyurethane foam, while also improving the thermal insulation performance of the polyurethane foam.

[0150] The compressive strength of Examples 8-9 is higher than that of Example 7, and the thermal conductivity is lower than that of Example 7, indicating that the present application further modifies the hollow glass microspheres to further improve the mechanical properties of the polyurethane foam, while also improving the thermal insulation performance of the polyurethane foam.

[0151] The compressive strength of Example 10 is higher than that of Example 7, and the thermal conductivity is lower than that of Example 7, indicating that the present application further controls the chopped length of the jute fiber, which can improve the dispersibility of the jute fiber in the polyurethane matrix resin, thereby further improving the mechanical properties of the polyurethane foam.

[0152] The compressive strength of Examples 11-12 is higher than that of Example 1, and the thermal conductivity is lower than that of Example 1, indicating that the application also adds carbon nanotubes to the white material, which can significantly improve the mechanical properties of the polyurethane foam and also improve the thermal insulation performance of the polyurethane foam.

[0153] The compressive strength of Example 13 is higher than that of Example 12, and the thermal conductivity is lower than that of Example 12, indicating that the present application further uses amino-modified carbon nanotubes to further enhance the mechanical properties of the polyurethane foam.

[0154] The compressive strength of Examples 14-17 is lower than that of Example 1, and the thermal conductivity is higher than that of Example 1, and cracking occurs on the surface, indicating that the application adopts a combination of dibutyltin dilaurate, pentamethyldiethylenetriamine, N,N-dimethylcyclohexylamine, tris(dimethylaminopropyl)hexahydrotriazine, Dabco 33-LV and potassium acetate catalysts to significantly improve the mechanical properties of polyurethane foam and reduce the possibility of core burning and cracking in polyurethane foam.

[0155] The compressive strength of Examples 18-19 is higher than that of Example 1, and the thermal conductivity is lower than that of Example 1, but the compressive strength is lower than that of Examples 6-7, and the thermal conductivity is higher than that of Examples 6-7, indicating that the present application further controls the usage of hollow glass microspheres and modified jute fibers, which can further improve the mechanical properties of polyurethane foam.

[0156] The compressive strength of Examples 20-21 is higher than that of Example 1, and the thermal conductivity is lower than that of Example 1, but the compressive strength is lower than that of Examples 11-12, and the thermal conductivity is higher than that of Examples 11-12, indicating that the present application further controls the amount of carbon nanotubes used, which can further improve the mechanical properties of polyurethane foam.

[0157] The compressive strength of comparative examples 1-5 is significantly lower than that of example 1, and the thermal conductivity is significantly higher than that of example 1, indicating that the present application adopts a mixed use of multiple polyether polyols, which can significantly improve the mechanical properties of polyurethane foam and reduce the possibility of core burning and cracking.

[0158] The compressive strength of Comparative Examples 6-7 is significantly lower than that of Example 1, and the thermal conductivity is significantly higher than that of Example 1, indicating that the present application further controls the ratio between polyether polyols to further improve the mechanical properties of polyurethane foam.

[0159] The compressive strength of comparative examples 8-9 is significantly lower than that of example 1, and the thermal conductivity is significantly higher than that of example 1, indicating that the present application further controls the ratio between the black material and the white material, and can further improve the mechanical properties of the polyurethane foam.

[0160] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A fully water-foamed polyurethane for thermal insulation pipes, characterized in that: The raw materials used for the polyurethane include black material and white material in a weight ratio of (100-150):100; the black material is polymethyl polyphenyl polyisocyanate; The white material comprises the following components in parts by weight: Polyether polyol A 30-50 parts; Polyether polyol B 10-20 parts; Polyether polyol C10-50 parts; Polyether polyol D 10-20 parts; Polyether polyol E 0-20 parts; 2-8 parts of catalyst; 1-3 parts of foam stabilizer; 1-3 parts water; The polyether polyol A has a functionality of 4.5-6, a hydroxyl value of 360-450 mgKOH / g, and a viscosity of 5000-12000 map·s; The polyether polyol B has a functionality of 3-5, a hydroxyl value of 500-1200 mgKOH / g, and a viscosity of 600-1600 map·s; The polyether polyol has a C functionality of 3.5-4.5, a hydroxyl value of 320-380 mgKOH / g, and a viscosity of 700-1500 map·s; The polyether polyol D has a functionality of 3-4, a hydroxyl value of 300-500 mgKOH / g, and a viscosity of 2000-4000 map·s; The polyether polyol E has a functionality of 2-3, a hydroxyl value of 300-400 mgKOH / g, and a viscosity of 2000-30000 map·s; The catalyst includes dibutyltin dilaurate, pentamethyldiethylenetriamine, N,N-dimethylcyclohexylamine, tris(dimethylaminopropyl)hexahydrotriazine, Dabco 33-LV and potassium acetate catalyst in a weight ratio of (0.01-0.02):(0.1-2):(0.1-3):(0.1-4):(0.1-3):(0.1-2).

2. The fully water-foamed polyurethane for heat-insulating pipes according to claim 1, characterized in that: The weight ratio of the black material to the white material is (135-140):

100.

3. The fully water-foamed polyurethane for thermal insulation pipe according to claim 1, characterized in that: The white material also includes 1.08-4.38 parts by weight of hollow glass microspheres and 1.35-5.47 parts by weight of jute fibers modified by a silane coupling agent.

4. The full water foamed polyurethane for heat-insulating pipe according to claim 3, characterized in that: The hollow glass microspheres are modified by the following method: First, immerse the hollow glass microspheres in acetone, then dry the hollow glass microspheres at a temperature of 110-120°C, and then soak the hollow glass microspheres in a silane coupling agent with a mass fraction of 0.5-2% for 15-20 minutes, then filter, and dry at a temperature of 110-120°C for 1-2 hours to obtain modified hollow glass microspheres.

5. The full water foamed polyurethane for heat-insulating pipe according to claim 3, characterized in that: The jute fiber has a chopped length of 1.8-2.0 mm.

6. The fully water-foamed polyurethane for heat-insulating pipes according to claim 1, characterized in that: The white material also includes 1.5-4.5 parts by weight of carbon nanotubes.

7. The full water foamed polyurethane for heat-insulating pipe according to claim 6, characterized in that: The carbon nanotubes are amino-treated carbon nanotubes.

8. The full water foamed polyurethane for heat-insulating pipe according to claim 1, characterized in that: The foam stabilizer is a silicon surfactant.

9. A method for preparing the fully water-foamed polyurethane for thermal insulation pipe according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix all the components in the white material to obtain a mixture; S2. Under the conditions of a temperature of 15-35°C and a rotation speed of 2500-2600r / min, the mixed material and the black material are mixed and stirred evenly to obtain a fully water-foamed polyurethane.